Network coverage modeling for the placement of telecommunication towers using remote sensing data from aerial surveys - Bakó, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2016)
The design of the landscape, environmental and economical approach to investment planning requires the most modern methods of data collection and modeling. Cost-efficient photogrammetric survey provides data for the optimal installation of telecommunication base stations. Cost efficient areal photogrammetric surveys can yield spatial data that can running simulations and providing maps with planned tower locations. With the help of these databases the complex analysis of network coverage can be carried out. The method, however, is useful not only for new installations. For example, if due to any reason a base station becomes inoperative, the field strength will not only worsen at the very spot but also in the area of the surrounding cells, as these have to take over the partial provision in such a large area they cannot perform the original quality in their own territory. Therefore, the modelling process can also be very important in selecting the substitution tower locations.
Keywords: base stations; mobile services; telecommunications; modeling; remote sensing; landscape protection